Influence of postoperative pain and use of NSAID on heart rate variability of dairy cows. Issue 1 (February 2018) - Frondelius, Lilli; Hietaoja, Juha; Pastell, Matti; Hänninen, Laura; Anttila, Paula; Mononen, Jaakko
Abstract : This Research Communication describes the effect of post-operative pain and non-steroidal anti-inflammatory drug (NSAID) treatment on heart rate variability (HRV) of dairy cows. Postoperative pain in farm animals is often left untreated, and HRV could be a promising tool for assessing pain. The aim of this study was to assess if postoperative state after subcutaneous surgery affects HRV in dairy cows and to determine whether this could be modulated by NSAID. Nine cows were inserted with an implantable electrocardiograph logger. Cows were divided into the NSAID treatment group and the control group. The cows in the NSAID group had higher HRV than the control group, indicating a higher sympathetic activity in control animals, most likely due to untreated post-operative pain. Besides the ethical need for treating pain in production animals, ongoing pain has an adverse effect on animal productivity. Thus post-operative pain alleviation is recommended.